MGMT promoter methylation as a potential prognostic marker for acute leukemia - Sobieszkoda, Dominika (Arch Med Sci, 2017)
INTRODUCTION: It has been proved that genetic and epigenetic changes play a significant role in the development and progression of acute leukemia. The aim of our study was to evaluate the frequency and prognostic implications of genetic and epigenetic alterations in p15, MGMT, DNMT3A and TP53 genes in acute leukemias. MATERIAL AND METHODS: We included in the study 59 patients with acute leukemia. Evaluation of TP53 and DNMT3A mutations was performed using sequencing analysis and PCR-RFLP, respectively. Methylation status of MGMT and p15 genes was evaluated using MSP and COBRA, respectively. For assessment of global DNA methylation ELISA-based kit was used. RESULTS: We found that overall survival was higher for ALL patients. MGMT promoter methylation was significantly associated with patients age at the time of diagnosis (p = 0.03). TP53 and DNMT3A mutations were observed only in AML patients (16.67% and 8.8%, respectively). Patients with acute leukemia and p15 promoter methylation had significantly more frequently mutated TP53 gene (p = 0.04) and AML patients with p15 promoter methylation had significantly more frequently detected global hypomethylation of DNA (p = 0.009). In the group of ALL patients we noted an opposite trend: only patients negative for p15 promoter methylation were characterized by global DNA hypomethylation. CONCLUSIONS: Our findings demonstrate that MGMT promoter methylation can have a considerable impact on the development of acute leukemia in older patients. DNMT3A and TP53 mutations may play a significant role in AML development. However, further studies conducted in a larger cohort of patients are needed to determine its clinical utility.